Removal of Sulphate and Manganese on Synthetic Wastewater in Sulphate Reducing Bioreactor Using Indonesian Natural Zeolite - Endah Retnaningrum; Wahyu Wilopo (Universitas Gadjah Mada, 2017)
The present research was conducted to investigate sulphate and manganese removal from synthetic wastewater. The continuous laboratory scale of down-flow fluidized-bed reactor (DFBR) using sulphate reducing bacteria (SRB) consortium and Indonesian natural zeolite as a bacterial support material was designed. At 9 days operation, maximum sulphate and manganese removal was observed to be 23% and 15.4%, respectively. The pH values were also changed to neutral. The population of SRB increased which effect on the raising of their activity for removing sulphate and manganese. Using the scanning electronic microscopy (SEM), it was observed that natural zeolite possesses excellent physical characteristics as a bacterial support material in DFBR. The imaging SEM result of SRB consortium on zeolite surface clearly showed the developed SRB biofilm on that particle. Analysis result of EDX confirmed that manganese was precipitated as manganese–sulfides.